Global access to antibiotics without prescription in community pharmacies: A systematic review and meta-analysis - Auta, A.; Hadi, M.A.; Oga, E.; Adewuyi, Emmanuel; Abdu-Aguye, S.N.; Adeloye, D.; Strickland-Hodge, B.; Morgan, D.J. (2019)
Objective: To estimate the proportion of over-the-counter antibiotic requests or consultations that resulted in non-prescription supply of antibiotics in community pharmacies globally. Methods: We systematically searched EMBASE, Medline and CINAHL databases for studies published from January 2000 to September 2017 reporting the frequency of non-prescription sale and supply of antibiotics in community pharmacies across the world. Additional articles were identified by checking reference lists and a Google Scholar search. A random effects meta-analysis was conducted to calculate pooled estimates of non-prescription supply of antibiotics. Results: Of the 3302 articles identified, 38 studies from 24 countries met the inclusion criteria and were included in the review. All the included countries with the exception of one, classified antibiotics as prescription-only medicines. The overall pooled proportion of non-prescription supply of antibiotics was 62% (95% CI 53–72). The pooled proportion of non-prescription supply of antibiotics following a patient request was 78% (95% CI 59–97) and based on community pharmacy staff recommendation was 58% (95% CI 48–68). The regional supply of non-prescription antibiotics was highest in South America, 78% (95% CI 72–84). Antibiotics were commonly supplied without a prescription to patients with symptoms of urinary tract infections (68%, 95% CI 42–93) and upper respiratory tract infections (67%, 95% CI 55–79). Fluoroquinolones and Penicillins respectively were the most commonly supplied antibiotic classes for these indications. Conclusion: Antibiotics are frequently supplied without prescription in many countries. This overuse of antibiotics could facilitate the development and spread of antibiotic resistance.